Food Engineering within Sciences of Food - Athanasios Kostaropoulos (International Journal of Food Studies)
The aim of this paper is to clarify the identity of food engineering in sciences of food. A short historical description of the evolution of the branch in the Anglo Saxon and the Continental educational systems is given. Furthermore, the distinction of basic definitions such as food science, food science and technology, food technology, and food engineering is made. Finally, the objectives of food engineering within the branch of sciences of food are described.